In-silico drug repositioning studies of Candida albicans Nitrogen permease reactivator 1 (Npr1) kinase - Sanjib Das; Arka Bagchi; Analava Bera; Arunima Biswas; Analabha Roy; Rik Ganguly; Amalesh Mondal; Deepanjan Chattopadhyay; Paromita Saha Mondal; Tanushree Mondal; Subhasree Samanta; Achintya Mohan Goswami; et al. (Scientific Reports)
Abstract Npr1 is an essential protein in C. albicans, maintains ion homeostasis and nutrient transportation at cell membrane, and regulates the activity of ammonium transporter protein Mep2. Npr1 is one of the nine NPR/HAL family kinases classified under “Other groups” in C. albicans. In this study, we had performed protein homology modeling; structure based virtual screening of drugs, docking study and MD simulation. We employed drug repurposing pipeline from which 15 compounds were short listed. Among the compounds, Indacaterol was selected on the basis of high safety profile, binding affinity score value of − 9.3 kcal/mol, as well as its DFG-motif interaction. The best docked pose of the complex was utilized for MD simulation studies. The RMSD values from initial structure and protein–ligand complex were analyzed for the dynamic stability of drug-bound complex and compared with that of the apo-protein. The comparisons of average RMSF values show fluctuation within acceptable range, also very less change of Rg values occur between the protein and protein–ligand throughout the simulation. Further, the complex maintains on an average two hydrogen bonds throughout the simulation period. The binding stability of Npr1 and Indacaterol complex was also verified through Principal Component Analysis. The result secured from these computational approaches and techniques established that the drug has the potential to be developed as an anti-candida lead targeting candidiasis.